2013
DOI: 10.1371/journal.pone.0055318
|View full text |Cite
|
Sign up to set email alerts
|

Recanalization of Extracranial Internal Carotid Artery Occlusion after i.v. Thrombolysis for Acute Ischemic Stroke

Abstract: BackgroundAlthough extracranial internal carotid artery (e-ICA) occlusion is a common pathology in patients undergoing intravenous thrombolysis for treatment of acute ischemic stroke, no data on e-ICA recanalization rate or potential effects on outcome are yet available.Methods and ResultsThis study included 52 consecutive patients with e-ICA occlusion and ischemic stroke undergoing standard intravenous thrombolysis. The rate of e-ICA recanalization was 30.8% [95%CI, 18.2–43.3], documented at 3.5 [2.0–11.8] (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…IV thrombolysis or IA thrombolysis using rtPA in these patients is usually ineffective. Pechlaner et al 3 reported that approximately one-third of patients had extracranial ICA occlusion recanalized after IV thrombolysis within a median of 3.5 days after stroke, but the clinical outcome was not significantly better than patients who did not receive IV thrombolytic therapy. In addition, Ratanaprasatporn et al 23 reported that, in patients with AIS with concomitant cervical carotid and intracranial occlusion, IA thrombolysis using rtPA after revascularization of the cervical ICA with CAS increased the rate of recanalization compared with patients given IA thrombolysis via the collateral circulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IV thrombolysis or IA thrombolysis using rtPA in these patients is usually ineffective. Pechlaner et al 3 reported that approximately one-third of patients had extracranial ICA occlusion recanalized after IV thrombolysis within a median of 3.5 days after stroke, but the clinical outcome was not significantly better than patients who did not receive IV thrombolytic therapy. In addition, Ratanaprasatporn et al 23 reported that, in patients with AIS with concomitant cervical carotid and intracranial occlusion, IA thrombolysis using rtPA after revascularization of the cervical ICA with CAS increased the rate of recanalization compared with patients given IA thrombolysis via the collateral circulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical outcome after medical treatment is usually very poor in cases of AIS induced by occlusion or stenosis of the proximal internal carotid artery (ICA) that results in severe neurological symptoms and is usually not accessible by recombinant tissue plasminogen activator (rtPA) thrombolysis 2 3. In recent years the feasibility, safety and effectiveness of emergency carotid artery stenting (eCAS) with/without additional intra-arterial (IA) thrombolysis/thrombectomy have been studied extensively and both technically and clinically promising results have been reported 4–17.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with carotid occlusion–associated stroke have high rates of death and disability but treatments are limited. Successful recanalization with intravenous tissue plasminogen activator (tPA), the current stroke thrombolytic, is only achieved in 10% to 30% of patients with carotid occlusion 1, 2, 3. Although a severe carotid stenosis predicts a greater risk of stroke for any individual,4 the population frequency of mild stenosis is greater.…”
Section: Introductionmentioning
confidence: 99%
“…One previous retrospective study showed that a high-grade stenosis remained in 13 (25%) of 52 patients with an acute occlusion. 18 Two smaller studies reported a residual high-grade stenosis in 1 of 12 (8.3%) patients and 2 of 20 (10.0%) patients, respectively. 2,16 More than half of the patients with a residual high-grade stenosis in our study population underwent CEA or carotid stenting.…”
Section: Discussionmentioning
confidence: 95%
“…2,[16][17][18] The rate of recanalization is dependent on several factors, such as the type of acute treatment and the segment affected. 17,19 This is the first study with a prospective design on the occurrence of a residual high-grade stenosis after recanalization of an extracranial ICA occlusion in the acute stage of cerebral ischemia.…”
Section: Discussionmentioning
confidence: 99%